Anxious about Cholesterol - Conquer with Homoeopathic Modality (Homoeopathy for All, 2023)
lipids & lipoproteins in the blood has  become a common clinical problem  of the century which has turned out  to be a challenge to the physician.  Maintaining healthy Cardio vascular  system  is a significant part of maintaining good quality of life.  Cholesterol plays a vital role in  getting cardiac diseases with more  prevalence. This article provides  an overview of the aetiology,  diagnosis, and appropriate general  & homoeopathic management of  this Cholesterol disorder.
Keywords: Anxious; Cholesterol